2019
DOI: 10.1029/2019jb017764
|View full text |Cite
|
Sign up to set email alerts
|

Linear Relationship Between Aftershock Productivity and Seismic Coupling in the Northern Chile Subduction Zone

Abstract: The aftershock productivity is known to strongly vary for different mainshocks of the same magnitude, which cannot be simply explained by random fluctuations. In addition to variable source mechanisms, different rheological properties might be responsible for the observed variations. Here we show, for the subduction zone of northern Chile, that the aftershock productivity is linearly related to the degree of mechanical coupling along the subduction interface. Using the earthquake catalog of Sippl et al. (2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
5
24
0
Order By: Relevance
“…Aftershocks activity has been related to fault properties as state of stress (Shebalien & Narteau, 2017), rupture processes (Poli et al, 2016), seismic coupling (Hainzl et al, 2019) and the thermal state of the slab, with colder slabs showing a greater number of aftershocks (Wiens & Gilbert, 1996). A main issue is to understand if this general decrease in the number of aftershocks is real, or it is due to the lack of near-field data (Li et al, 2018).…”
mentioning
confidence: 99%
“…Aftershocks activity has been related to fault properties as state of stress (Shebalien & Narteau, 2017), rupture processes (Poli et al, 2016), seismic coupling (Hainzl et al, 2019) and the thermal state of the slab, with colder slabs showing a greater number of aftershocks (Wiens & Gilbert, 1996). A main issue is to understand if this general decrease in the number of aftershocks is real, or it is due to the lack of near-field data (Li et al, 2018).…”
mentioning
confidence: 99%
“…The relationship between the seismicity parameters that describe aftershock generation and the geophysical features in the seismogenic zone has been explored by previous studies (e.g., Mogi 1967;Ogata 2004;Marsan and Helmstetter 2017;Nandan et al 2017;Zakharova et al 2017;Hainzl et al 2019). For example, Ogata (2004) suggested that aftershock productivity ( ) is high on the boundary of each source region that hosts M7-class earthquakes along the subduction zone, offshore NE Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed the relationship between the observed seismicity and geophysical features in the seismogenic zone (e.g., Ogata 2004;Nandan et al 2017;Zeng et al 2018;Ben-Zion and Zaliapin 2019;Hainzl et al 2019). For example, Zeng et al (2018) demonstrated that spatial variations in the background seismicity rate in California correlate with the maximum shear strain rate, and Ogata (2004) suggested that aftershock productivity (one of the parameters that define the modified Omori law) is high on the boundary of the source region hosting M7-class earthquakes along the offshore Tohoku region.…”
Section: Introductionmentioning
confidence: 99%
“…Marsan and Helmstetter (2017) investigated the fluctuations of aftershock productivity in Southern California, and related the results to the stress drop variability of mainshocks. Hainzl et al (2019) found a linear relationship between the aftershock productivity and the coupling coefficient in the Chile subduction zone.…”
mentioning
confidence: 89%
“…Hainzl et al. (2019) found a linear relationship between the aftershock productivity and the coupling coefficient in the Chile subduction zone.…”
Section: Introductionmentioning
confidence: 99%